La disciplina deportiva del baloncesto y su influencia en el desarrollo de los valores sociales en los estudiantes de la Unidad Educativa Francisco Huerta Rendón 2015- 2016 - Cerezo Flores, Víctor Rodrigo (2016)
In this research we can analyze social values applied in basketball and its influence on society, it will try to relate social dimensions of sport from the effects that this produces in daily life and in basketball because of its dynamism and frequency of scoring actions it is one of the sports with the highest number of spectators and a system of rules that marks its internal dynamics and physical activity. This work was aimed to analyze how the sport of basketball influences the development of social values of students of the Education Unit Francisco Huerta Rendón through field research in the same development guide axiológica was observed values the same that was implemented in the field during the development of each of the commitments which were observed and results were validated using the test chip squared to determine whether there is a relationship between the result of commitments and axiological values applied in the matches, so we need to synthesize that playing basketball is a field of action very productive for teaching and application of values such as respect, companionship, solidarity, honesty, tolerance and equality as a fundamental axis students Education Unit Francisco Huerta Rendón.